Development of an Organizational Compassion Model Based on Employee Behavior in Service-Oriented Organizations: A Content Analysis Approach - Asgarpour Gazafroudi, Zahra; Pali, Samira; Saeidian Khorasgani, Narges (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective: The purpose of this study is to present an organizational compassion model based on employee behavior in service-oriented organizations. Methods and Materials: This research is descriptive-analytical in terms of data collection methods and inductive-deductive in terms of research approach. Semi-structured interviews were conducted with 19 experts. Data saturation was observed after the 17th interview; however, interviews continued up to the 19th to ensure complete saturation of the data. The interviews were semi-structured, with questions pertaining to the levels and components of the conceptual model. All interviews were recorded, and after each interview, data analysis was conducted to establish the model. The qualitative data analysis process involved coding. Initially, the content of all interviews was transcribed, followed by open coding. The collected interview data were transcribed onto paper, and line-by-line and segment-by-segment analysis was performed to generate open codes. After editing, the open codes were direct quotations from the texts or, in some cases, verbatim excerpts. Findings: From the analysis of 19 interviews, a total of 378 initial codes were extracted. After analyzing the interview texts, 55 selective codes and 12 sub-themes were identified. In the final stage, through examination of the organizing themes, six main themes or overarching themes were identified: Organizational Perception and Human Sensitivity; Compassionate Management Response; Organizational Action and Intervention; Culture and Institutionalization of Compassion; Collective Compassion and Interpersonal Relationships; and Behavioral and Psychological Outcomes. Conclusion: This study establishes a comprehensive organizational compassion model for service-oriented entities, demonstrating how structured compassion practices enhance employee well-being, reduce burnout, and elevate service quality.